KETIDAKPASTIAN DAN KOMPLEKSITAS RANTAI PASOK DALAM KINERJA OPERASIONAL YANG BERKELANJUTAN - Hartanto, Soni (JEA17: Jurnal Ekonomi Akuntansi, 2021)
The purpose of this research plan is analyzing the different types of uncertainties and complexity in the supply chain and provide suggestion on strategies to deliver superior operational performance (OP) in disruption and dynamic situation using symmetrical and asymmetrical modeling approaches. Symmetrical modeling is applied via PLS-SEM in order to assess the theoretical relationships among the latent variables, while asymmetrical modeling is applied via fuzzy set qualitative comparative analysis (fsQCA) to emphasize their combinatory causal relation.  This research contributes by providing an illustration of a PLS-SEM and fsQCA based estimation for the rapidly emerging field of sustainable supply chain management. This study assumes to provide empirical support for resource dependence theory (RDT) in explaining the relation between SCU and SCS as well as SCO and SCC which leads to sustainable OP.  From a methodological standpoint, this study also illustrates predictive validation testing of models using holdout samples and testing for causal asymmetry.